Final cut Pro X quick-reference guide - Boykin, Brendan (Apple Pro training series., 2012)
Ideal for students and editors on the go, this is the quick look-up guide you've been hunting for. Veteran trainer Brendan Boykin uses clear, concise explanations and an easy-to-use format to walk you through the brand new Final Cut Pro X interface and put the essential techniques, most-used tools, and most-efficient workflows at your fingertips. A compendium of Final Cut Pro best practices, tips, and quick-glance reminders, plus a great summary of what's new in Final Cut Pro X. This e-book Quick-Reference Guide will also be included in the following DVD/book package: Apple Pro Video Series: Final Cut Pro X, ISBN: 0321809629, presented by Steve Martin.